Additional measures on the development of the conditions of competition on the Russian electricity market - V. Ya. Afanasev; V. V. Kuzmin (Вестник университета)
The issues of the organization of relations in the modern Russian electric power market have been considered. Based on the analysis of the characteristics and problems of the current model of the Russian electricity market, the conclusion has been made, that it is necessary to develop and implement an additional set of measures to develop this market in order to ensure acceptable conditions of competition, which allow through application of the competitive procedures and mechanisms to increase the efficiency of the electric power production, transmission and consumption process. The characteristic of the electric power market model, possessing the properties of modern markets with developed competition, has been given. The measures for the organizational and theoretical provision of the process of further development of the electric power market have been offered.